Double-Network-Layer, a New Solution for IPng - Shi Li (Dianxin kexue)
Traditional IPng solution——IPv6, extends the address space by extending the length of the address laterally. Thus it's incompatible with IPv4 and difficult to promote. A new solution: reuse the IP addresses by extending the protocol stack longitudinally was presented. In this way, it can not only get very big address space, but also have very good compatibility with current IPv4 network. So the upgrade has minimal impact, requires a minimum investment, and can be quickly deployed.